A high frequency of MDSCs in sepsis patients, with the granulocytic subtype dominating in gram-positive cases. Issue 5 (13th June 2014) - Janols, Helena; Bergenfelz, Caroline; Allaoui, Roni; Larsson, Anna-Maria; Rydén, Lisa; Björnsson, Sven; Janciauskiene, Sabina; Wullt, Marlene; Bredberg, Anders; Leandersson, Karin
Abstract : The causative microorganism dictates the type of MDSC generated in sepsis patients; a large proportion of PMN-MDSCs in gram-positive sepsis are immunosuppressive myeloid blasts. ABSTRACT: The causative microorganisms dictate the type of MDSC generated in sepsis patients, and a large proportion of PMN-MDSCs in gram-positive sepsis includes immunosuppressive myeloid blasts. MDSCs constitute a heterogeneous population of immature myeloid cells that potently suppress immune responses. They were identified originally in cancer patients and have since been reported to occur also in chronic inflammation, autoimmunity, and even bacterial infections. Human MDSCs are commonly divided into Mo-MDSCs and granulocytic (PMN-MDSCs) subtypes. To what extent the bona fide cancer MDSCs are representative of the proposed MDSCs found in other diseases is not well known. PMN-MDSCs have been found previously to be enriched among LDGs in density gradient-centrifuged blood. In this study, we analyzed potential MDSCs in sepsis patients with different causative microorganisms, using total peripheral blood compared with density gradient-centrifuged blood. We found a high frequency of typical CD14 + HLA-DR low Mo-MDSCs in all sepsis patients, whereas the typical PMN-MDSCs, as well as a prominent CD14 low PMN-MDSC-like population, appeared preferentially in gram-positive cases. The CD14 low PMN-MDSC variant was demonstrated to suppress T cell proliferation in vitro via a ROS-dependent mechanism, to display an increased IL-10:TNF-α ratio, and to present with signs of immaturity: blast morphology and low cytokine levels. We conclude that a spectrum of cells with MDSC features is enriched in sepsis and that the microbial origin of sepsis contributes to the substantial interindividual patient variation in the MDSC pattern.